KAJIAN PENGARUH PENAMBAHAN LIDAH BUAYA (Aloe vera) TERHADAP MUTU SABUN TRANSPARAN - Erliza Hambali, Ani Suryani dan Evimia Indriani Umiarti (Jurnal Teknologi Industri Pertanian, 2004)
ABSTRACTAloe vera gel consist of saponin and lignin which has characteristic to clean dirt from skin, soften and give smoothness to skin. Based on that fact then, Aloe vera could be used on transparent soap which in return could give an additional value to the product and increase selling point and the benefit from aloe vera plant as one of agriculture commodity with high export potential.The addition of Aloe vera in the transparent soap formula will affect the quality of product. The analysis of variance at confidence interval of 95% (α= 0,05) has shown that the addition of aloe vera significantly affects to the water content and volatile substance, insoluble matter in alcohol, pH value and foam stability. The analysis of variance at confidence interval of 95% (α= 0,05) has shown that the addition of Aloe vera not significantly affect to fatty acid content, unsaponifiables fraction content, free alkali content which counted as NaOH content, mineral oil content and emulsion stability. It means that the addition of Aloe vera gave the same respond for those parameters. Key words :